2017
DOI: 10.1093/jhered/esx034
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Genetic Processes Influence MHC Evolution in Threatened Gopher Tortoises (Gopherus polyphemus)

Abstract: Levels of adaptive genetic variation influence how species deal with environmental and ecological change, but these levels are frequently inferred using neutral genetic markers. Major histocompatibility complex (MHC) genes play a key role in the adaptive branch of the immune system and have been used extensively to estimate levels of adaptive genetic variation. Parts of the peptide binding region, sites where MHC molecules directly interact with pathogen and self-proteins, were sequenced from a MHC class I (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…We recovered high MHC class I α polymorphism in both species based on sequence diversity and number of recovered alleles. Low immunogenetic diversity following population bottlenecks has been documented in amphibians [89], birds [90] and non-avian reptiles [53]; however, despite historical reductions in Ch. mydas population sizes [31] and threats to Ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recovered high MHC class I α polymorphism in both species based on sequence diversity and number of recovered alleles. Low immunogenetic diversity following population bottlenecks has been documented in amphibians [89], birds [90] and non-avian reptiles [53]; however, despite historical reductions in Ch. mydas population sizes [31] and threats to Ca.…”
Section: Discussionmentioning
confidence: 99%
“…However, this polymorphism is potentially overestimated, as the alleles we recovered come from multiple unidentified loci. By comparison, studies of Testudines that were able to assign MHC class I alleles to loci found that across 18 populations of Gopher tortoise ( Gopherus polyphemus ) at MHC class I exon 3, there were 13% segregating sites and nucleotide diversity was 0.03 [53]; furthermore, in a population of Diamondback terrapins ( Malaclemys terrapin ), the MHC class I locus was fixed for a single allele [50]. By contrast, our conservative criteria for retaining alleles means we are probably underestimating total alleles, and additional sea turtle MHC studies will almost certainly reveal further MHC class I α diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to acknowledge how particular pathogens affect immune genetic diversity and, vice versa, how genetic variation influences adaptation to emerging zoonosis, habitat fragmentation, and climate change [40]. MHC genes play an important role in the adaptive branch of the immune system and have been used extensively to estimate levels of adaptive genetic variation [41]. While innate immunity is an efficient first protection against many pathogens but rather less specific, adaptive (or acquired) immunity is a highly specific immune response, and its variability is subject to different selective pressures [30,31].…”
Section: Nucleotide Diversity In Important Immune Gene Groupsmentioning
confidence: 99%
“…However, it is important to acknowledge how particular pathogens affect immune genetic diversity and, vice versa, how genetic variation in uences adaptation to emerging zoonosis, habitat fragmentation, and climate change [32]. MHC genes play an important role in the adaptive branch of the immune system and have been used extensively to estimate levels of adaptive genetic variation [33]. While innate immunity is an e cient rst protection against many pathogens but rather less speci c, adaptive (or acquired) immunity is a highly speci c immune response, and its variability is subject to different selective pressures [22,23].…”
Section: Old World Camelids Genome Assemblies´ Improvementmentioning
confidence: 99%